Aux origines du capitalisme Robert Brenner et le marxisme politique - Allisson, François; Brisset, Nicolas (Feuillets : économie politique moderne, 2023)
How and when did the world enter the system we call "capitalism"? This is the question at the heart of the Brenner Debate, named after the American historian Robert Brenner. Robert Brenner's works have exerted a profound influence on the development of Marxist thought since the 1970's, elevating this debate among historians of capitalism to great significance. In the first part, François Allisson and Nicolas Brisset trace and contextualize the key stages of the debate, which led to Robert Brenner's seminal work. The authors demonstrate that one's approach to the history of capitalism is closely linked to one's view of the economic system. The second part contains a previously unpublished translation of Robert Brenner's 2007 article, « Propriété et progrès : quand Adam Smith faisait fausse route », which is according to its author the definitive version of his 1976 argument. This book is an introduction to the thought of an economist who is relatively unknown in the French-speaking world but who deserves our attention in view of his significant contributions to Anglo-Saxon historiography.